Carcass Characteristics of Growing Male Pig in Different Level of Clenbuterol Addition - Wayan Sukarya Dilaga (International Journal of Science and Engineering, 2013)
Abstract - Nowadays, pig has becomes an important role in meat supply chain and demand in the world. However, in the intensive maintenance system, raising pig still has problems especially in feed supplements. The investigation on carcass characteristics of growing male pig in different level of clenbuterol addition in feed was conducted. CRD factorial 2 x 3 with 4 repetitions was used in the experiment. The first factor is the nation's pig (L = local pigs & pig off spring K=imports) and the second factor is the level of clenbuterol (T0 = 0 mg/kg feed; T1 = 0.20 mg/kg feed & T2 = 0.40 mg/kg feed). The materials were 24 male grower pigs (12 local & 12 imported pigs) with 52.5 ± 28.27 kg body weight. Pigs were reared in individual cages for 6 weeks consisting 2 weeks for adaptation and 4 weeks for data collection. The pigs were given the same feed consisting of rice bran 27.8%, 55.5% and 16.7% corn concentrate. Feeding pigs was given in appropriate growth phase as much as 2 times a day. Drink provided using ad-libitum method. At the end of the study, the pigs were slaughtered. The meat was then analyzed based on the weight of the cut meat, weight of hot carcass, carcass percentage and carcass components (meat, bones and fat). The data was analyzed in variety followed by various orthogonal polynomial tests. Results shown that there were a real interaction between carcass weight and weight cut with quadratic pattern. Clenbuterol also found out to give an reduction effect on carcass percentage in both local and imported pig. In fact the local pigs give the lower carcass percentage than the imported one. Key Words – clenbuterol; weight cut; carcass percentag; carcass component Doi: 10.12777/ijse.5.2.47-50 [How to cite this article: Dilaga, W.S. (2013). Carcass Characteristics of Growing Male Pig in Different Level of Clenbuterol Addition. International Journal of Science and Engineering, 5(2):9-14. Doi: 10.12777/ijse.5.2.9-14]. Doi: 10.12777/ijse.5.2.47-50